2019
DOI: 10.3390/app9142880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particulate Disintegration on Biomethane Potential of Particle-Rich Substrates in Batch Anaerobic Reactor

Abstract: An investigation of particle disintegration was carried out using batch anaerobic reactors and a particle-rich substrate from pig manure supernatant. Two types of samples were applied, one high in suspended particles (raw feed) and another low in suspended particle content (centrifuged feed). Both feeds were digested with and without cellulase enzyme addition to obtain a better understanding of particle degradation mechanisms. An automatic methane potential test system (AMPTS) was used to carry out batch react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Comparison of the two modes of simulations revealed that classification of particles into fast and slow disintegrating fractions (Mode 2) led to a better representation of the experimental data compared to Mode 1 simulation across all four phases of the experiment. Application of the same simulation approaches to batch reactors also revealed that Mode 2 simulation led to a better fit to experimental observations [9]. Mode 1 simulation assumed that all particulates possess fast disintegration potential, whereas Mode 2 assumed that a fraction of the particulates disintegrated at a slower rate based on Equation (4).…”
Section: Simulation Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Comparison of the two modes of simulations revealed that classification of particles into fast and slow disintegrating fractions (Mode 2) led to a better representation of the experimental data compared to Mode 1 simulation across all four phases of the experiment. Application of the same simulation approaches to batch reactors also revealed that Mode 2 simulation led to a better fit to experimental observations [9]. Mode 1 simulation assumed that all particulates possess fast disintegration potential, whereas Mode 2 assumed that a fraction of the particulates disintegrated at a slower rate based on Equation (4).…”
Section: Simulation Resultsmentioning
confidence: 92%
“…In this article, we intend to demonstrate that first-order disintegration and hydrolysis kinetics can accurately model the anaerobic digestion of complex substrates by classifying complex particulates into fast and slow disintegrating sections. We demonstrated the effectiveness of this approach in batch anaerobic reactors [9].…”
Section: Particle Disintegration and Hydrolysismentioning
confidence: 91%
“…As a common co-substrate, animal manures are particulate organic-rich materials with negative effects on the kinetics of the anaerobic process. The effect of enzymatic (cellulase) pretreatment on particulate disintegration of this waste was studied by Tassew et al [10]. Moreover, the review by Ahmed et al [11] offers an in-depth insight into hydrothermal pretreatment with a section dedicated to inhibitors formed by the delignification process (mainly furfural and 5-HMF) and strategies to overcome it.…”
Section: Pretreatments In the Hotspotmentioning
confidence: 99%